From Philosophical Reinterpretation to Operational Unity: A Mixed-Methods, International Lunar Date Line–Anchored Framework for a Pre-Calculated Global Hijri Calendar (Imkān al-Ruʾyah) - Abdul Halim Bin Abdul Aziz; Alim Roswantoro (Living Islam: Journal of Islamic Discourses, 2025)
This study examines whether—and how—a pre-calculated, single, uniform Hijri calendar can be justified from Qur’an and Hadith and operationalized with established astronomical rules. It addresses persistent disunity arising from fragmented practices in a highly interconnected “global village.” A mixed-methods design integrates: (i) a normative–conceptual analysis via Khaled Abou El Fadl’s negotiative method (text–author–reader) to derive scriptural bounds (twelve lunar months without intercalation; calculability; 29/30-day months; hilal as civil mīqāt; semantic range of ra’ā); and (ii) a computational–astronomical evaluation of a two-condition global rule anchored in the International Lunar Date Line (ILDL): S1—global conjunction occurs before local sunset along the IDL (~180°E; ±20° lat), and S2—an imkān al-ru’yah threshold is met on a 60°W test line (±20°; prototype 0.52% illumination). Topocentric ephemerides with standard parallax/refractive corrections (UTC, ΔT) are used, with ~500-year robustness checks and comparisons to regional criteria (e.g., MABIMS). Scriptural analysis legitimizes the use of information/calculation for dating while respecting Sunnah. The two-condition scheme prevents pre-conjunction starts (S1) and ensures expected visibility on the same day (S2). Simulations over ~500 years converge to the lunar synodic mean (~29.53 days) and align with the concept of ḥukmī ru’yah and Istanbul 2016 recommendations. Implementation mapping shows regional variation is historically instrumental; an IDL-anchored global maṭla‘ is operationally coherent. The study unifies a scripturally anchored rationale with ILDL-based imkān into a testable, auditable global rule and a realistic pathway for majority/minority contexts. Adoption of the two-condition rule, supported by a cross-national astronomy–fiqh clearing house and multi-year calendars, can synchronize worship dates and public services. Education systems benefit through stable academic calendars, assessment schedules, and digital platform integration across jurisdictions.